DESIGN AND CONSTRUCTION OF OPERATIONAL PERFORMANCE INDICATORS OF ROTARY KILNS - Fedoriv, Viktor; Stechyshyn, Myroslav; Martynyuk, Andrii; Liukhovets, Volodymyr; Mankov, Viktor; Stepanets, Oleksii (SWorld-Ger Conference proceedings, 2025)
This article discusses the problems of baking bakery products. In the bread baking production line, the oven occupies a leading position. This is due to the fact that the entire complex of processes related to the production of bread is completed in the o